Health Matters - Coasters Association (2007)

Remembering our Heritage and Culture - Fequet Griffin, Priscilla (Coasters Association, 2003)
The project started on June 16, 2003, at which time a schedule of activities was produced (see annex 1). Following this, a list of all seniors (65 and up), within the Municipality of Bonne Esperance, was developed containing their ages and phone numbers (see annex 2). All seniors were contacted for their participation in this project, in which all ninety-nine were willing to take part.